2021
DOI: 10.3390/polym13081335
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Application of the Hydrophobic Polyurethane Foam: Expansive Soil Stabilization

Abstract: The reversible shrink–swell behavior of expansive soil imposes a serious challenge that threatens the overlying structures’ safety and durability. Traditional chemical additives such as lime and cement still exhibit satisfying performance over their counterparts in terms of swelling potential reduction. Nevertheless, significant concerns are associated with these chemicals, in addition to their environmental impact. This paper proposes a novel application of the closed-cell one-component hydrophobic polyuretha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In 2021, Al-Atroush et al [101] performed an extensive laboratory experiment to assess the efficiency of the closed-cell hydrophobic polyurethane foam in mitigating the high swelling and shrinkage response of montmorillonite content Na-bentonite clay. The results have shown that, even after several wet-shrink cycles, the polyurethane resin effectively reduced the swelling and shrinkage potential of the reactive expansive soil.…”
Section: Laboratory Investigations Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Al-Atroush et al [101] performed an extensive laboratory experiment to assess the efficiency of the closed-cell hydrophobic polyurethane foam in mitigating the high swelling and shrinkage response of montmorillonite content Na-bentonite clay. The results have shown that, even after several wet-shrink cycles, the polyurethane resin effectively reduced the swelling and shrinkage potential of the reactive expansive soil.…”
Section: Laboratory Investigations Datamentioning
confidence: 99%
“…It was found that degradation does not occur except in some instances. Different studies on the degradation of PUs to fungal attacks [100][101][102] revealed that polyester PU is more vulnerable to fungal and microbial attack than polyether PU. On the other hand, polyether PU is moderately resistant to fungal and microbial attacks.…”
Section: Durability and Environmental Aspectsmentioning
confidence: 99%
“…Polyurethane (PU) adhesives have strong polarity and chemical activity because of their urethane and isocyanate groups, so they can form strong bonding with substrates containing active hydrogen and a variety of pores, such as wood, leather, paper, fabric, ceramics, etc. Meanwhile, they can also have good chemical adhesion with some substrates with a smooth surface, such as metals, plastics, rubber, glass, etc. , Although traditional solvent-based PU adhesives play an important role in many fields, they cause serious pollution to the environment but also they will increase the full utilization of petroleum resources. In contrast, waterborne polyurethane (WPU) adhesive is characterized by non-toxicity, environmental protection, as well as safe storage and transportation. WPU adhesive is used in shoe-making, packaging, construction, automobile, medical and health care, aerospace, and a wide range of general bonding. However, the introduction of hydrophilic groups leads to the deterioration of water resistance, mechanical properties, and thermal stability of the WPU film; as a result, its application in some fields is limited. , …”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane gout materials have been used in several repair projects, including highway crack treatment, high-speed railway track slab raising, emergency reinforcement of water conservation projects, and repair of rigid pavement [15][16][17][18], as depicted in Figure 1. Similarly, closed-cell one-component hydrophobic polyurethane foam can be used to stabilize expansive soil [19], whereas polyurethane grouting materials are employed for repair of road and runway facilities [20]. The numerical analytical method has been utilized to investigate the performance of concrete materials under static loadings, which is considered isotropic and homogenous for numerical simulation [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%